Socio, Cultural and Psychographic Dimensions of Advertising – A Conceptual Framework - Sudharshan, R.; Jyothi, K.Arun (Indian Journal of Marketing, 2004)
Advertising is any paid form of non-personal presentation and promotion of ideas, goods, or services by an identified sponsor. The purpose of advertising is to bring the advertised and its features and uses to the notice of the consumers. It also serves a number of other allied objectives which include creation of image and goodwill of the firm, explaining the various uses of goods and services to the customers; enabling the producer to face competition, removal of doubts and reminding the users to buy the products/services and maintenance of scale demand.The purpose of this paper is to present a conceptual framework regarding socio, cultural, and psychographic dimensions of advertising.